2014
DOI: 10.1038/ismej.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

Reset of a critically disturbed microbial ecosystem: faecal transplant in recurrent Clostridium difficile infection

Abstract: Recurrent Clostridium difficile infection (CDI) can be effectively treated by infusion of a healthy donor faeces suspension. However, it is unclear what factors determine treatment efficacy. By using a phylogenetic microarray platform, we assessed composition, diversity and dynamics of faecal microbiota before, after and during follow-up of the transplantation from a healthy donor to different patients, to elucidate the mechanism of action of faecal infusion. Global composition and network analysis of the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 62 publications
5
139
2
2
Order By: Relevance
“…However, the microbiota similarities, both in short and long term, were still remarkably lower than previously observed for western adults by using the same microarray technique for microbiota assessment (JalankaTuovinen et al, 2011;Rajilić-Stojanović et al, 2013;Fuentes et al, 2014;Satokari et al, 2014). Furthermore, we found that the most predominant Figure 6 The development of core microbiota # .…”
Section: Discussionmentioning
confidence: 50%
“…However, the microbiota similarities, both in short and long term, were still remarkably lower than previously observed for western adults by using the same microarray technique for microbiota assessment (JalankaTuovinen et al, 2011;Rajilić-Stojanović et al, 2013;Fuentes et al, 2014;Satokari et al, 2014). Furthermore, we found that the most predominant Figure 6 The development of core microbiota # .…”
Section: Discussionmentioning
confidence: 50%
“…Invasions from pathogenic microbes have been relatively wellstudied because they are comparatively easy to track, in part, due to strong, observable impacts (1). A particularly well-studied example is the invasion of the human gut microbiota by pathogenic bacteria (6,7). We know, however, much less about invasion by nonpathogenic microbes, even though we have evidence that they do occur in nature.…”
mentioning
confidence: 99%
“…Clostridium difficile decreased from initial 4% to 0.2% after FMT. The low microbiota diversity in the patients increased to the diversity of the donors within 2 weeks (van Nood et al ., 2013; Fuentes et al ., 2014). A recent trial reproduced an 84% cure rate with faecal transplantation given as enema to 232 Canadian CDI patients, who were after intensive antibiotic pretreatment randomized to either fresh or frozen stool preparations, without difference in cure rate (Lee et al ., 2016).…”
Section: Introducing Beneficial Bacteria Into the Gut Microbiomementioning
confidence: 99%